2021
DOI: 10.1039/d1tc02196f
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for polychlorinated trityl radicals

Abstract: An organic free radical is a molecule with one or more unpaired electrons. Although most free radicals are highly reactive, chemists have developed a few families of so-called persistent organic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 142 publications
(126 reference statements)
1
36
0
Order By: Relevance
“…Our characterization of Zn­(II) tripyrrindione in solution, together with the fluorescence emission noted in earlier studies, indicated that the neutral zinc-bound tripyrrindione is indeed a new addition to the small cohort of stable radicals that are fluorescent at room temperature . Excitation at 599 nm elicits a bright emission at 644 nm in THF with a quantum yield of 0.23 ± 0.01 (Figure C).…”
Section: Tripyrrin-114-dionesupporting
confidence: 68%
See 1 more Smart Citation
“…Our characterization of Zn­(II) tripyrrindione in solution, together with the fluorescence emission noted in earlier studies, indicated that the neutral zinc-bound tripyrrindione is indeed a new addition to the small cohort of stable radicals that are fluorescent at room temperature . Excitation at 599 nm elicits a bright emission at 644 nm in THF with a quantum yield of 0.23 ± 0.01 (Figure C).…”
Section: Tripyrrin-114-dionesupporting
confidence: 68%
“…Our characterization of Zn(II) tripyrrindione in solution, together with the fluorescence emission noted in earlier studies, 31 indicated that the neutral zinc-bound tripyrrindione is indeed a new addition to the small cohort of stable radicals that are fluorescent at room temperature. 48 Excitation at 599 nm elicits a bright emission at 644 nm in THF with a quantum yield of 0.23 ± 0.01 (Figure 5C). The luminescence of [Zn(TD1 • )(H 2 O)] therefore rivals that of other radical emitters, such as halogenated triarylmethyl radicals 49 and dithiadiazolyl radicals, 50 that are investigated for the development of electroluminescent devices.…”
Section: Luminescence Of the Tripyrrindione Radicalmentioning
confidence: 99%
“…were the first long-lived p-radical derivatives reported almost exactly half a century ago, and despite the recent progress presented in this review, they are still the basis of the state-of-the-art p-radicals used in optics, electronics and magnetics. 39,298 TTM and PTM based D-A systems and their heteroatom derivatives have been particularly successful in optoelectronic applications delivering stable emission from the doublet excited state and facilitating record-breaking efficiencies in OLEDs, undoubtedly because of their superior steric protection and energetic stabilisation associated with kinetic and thermodynamic effects, respectively. Debate on inertness of the chlorine substituents on chlorophenylmethyl radicals regularly arises in the literature, and many of the published works correctly report variable degrees of dehalogenation during radical functionalisation (synthesis) and application (device operation).…”
Section: Discussionmentioning
confidence: 99%
“…1–3 Organic π-conjugated radicals are also the subject of intense research in materials science because of their electron spin, making them innovative alternatives for the basis of next-generation optoelectronics, for instance, in organic field-effect transistors (OFETs), 4–6 organic light-emitting diodes (OLEDs), or organic magnets. 4,5,7–27 Furthermore, these molecular materials also provide fundamental insights about the nature of chemical bonds and their delocalization in open-shell systems, in addition to their other features such as narrow HOMO–LUMO energy gaps, low-lying doubly-excited states, or redox amphoterism. 4,10,12,13,15,28,29…”
Section: Introductionmentioning
confidence: 99%